2020
DOI: 10.3892/or.2020.7512
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑126‑3p suppresses HeLa cell proliferation, migration and invasion, and increases apoptosis via the PI3K/PDK1/AKT pathway

Abstract: We previously reported that relative to normal cervical mucus, microRNA 126-3p (miR-126-3p) is present in significantly greater amounts in the cervical mucus of patients with overt cervical cancer or precursor lesions. Here, we investigated the effects of enforced miR-126-3p expression in the cervical cancer cell line, HeLa, on proliferation, migration, invasion, apoptosis and protein expression. We transfected HeLa cells with miR-126-3p miRNA and found that proliferation, migration and invasion by cell counti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 46 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…As shown in (Figure 4a,4b), Bcl-2 levels decreased markedly in cardiac myocytes subjected to hypoxia/ acidosis or aerobic acidosis, and the effects were blocked by KD of miR-126 in parallel with reduced apoptosis. The results suggest negative regulation of anti-apoptotic Bcl-2 by miR-126 in this model that is consistent with some previous results [41,43,44]. We quantified the expression levels of p38-MAPK and JNK in hypoxic/acidotic and aerobic-acidotic cardiac myocytes in the presence and absence of miR-126 KD.…”
Section: Roles For Bcl2 and Mapk/jnk In Mir-126-mediated Inflammation And Apoptosissupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in (Figure 4a,4b), Bcl-2 levels decreased markedly in cardiac myocytes subjected to hypoxia/ acidosis or aerobic acidosis, and the effects were blocked by KD of miR-126 in parallel with reduced apoptosis. The results suggest negative regulation of anti-apoptotic Bcl-2 by miR-126 in this model that is consistent with some previous results [41,43,44]. We quantified the expression levels of p38-MAPK and JNK in hypoxic/acidotic and aerobic-acidotic cardiac myocytes in the presence and absence of miR-126 KD.…”
Section: Roles For Bcl2 and Mapk/jnk In Mir-126-mediated Inflammation And Apoptosissupporting
confidence: 92%
“…Previous work from others and ourselves established key roles for Bcl-2, mitogen-activated protein kinase (MAPK) and c-Jun N-terminal kinase (JNK) in apoptosis pathways of cardiac myocytes exposed to redox stress, acidosis and simulated ischemia with and without reperfusion [35][36][37][38][39]. Regulatory roles for miR-126 have also been described in cancer cells undergoing Bcl-2-mediated apoptosis [40][41][42]. Therefore, we investigated a possible role for Bcl-2 in the miR-126/pH sensitive apoptotic pathway of cardiac myocytes described herein.…”
Section: Roles For Bcl2 and Mapk/jnk In Mir-126-mediated Inflammation And Apoptosismentioning
confidence: 99%
“…Previous research has revealed that PI3K/AKT signaling is a well-known driver of tumorigenesis, and activation of this pathway is closely associated with cancer migration, invasion, and EMT, making it accountable for the high aggressiveness of cancers [ 23 25 ]. PDK1 is one of the main components of the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, as an important protein of the PI3K/AKT signaling pathway, PDK1 can bind to the product of activated PI3K, PIP3. Afterwards, PDK1/PIP3 complex transfers to the cell membrane, in order to phosphorylate AKT and activate AKT signaling pathway ( 52 ). AKT signaling pathway activation can accelerate the release of pro-inflammatory factors and thus may lead to abnormal cell biological processes, such as excessive cell proliferation, decrease in cell proliferation and increase in cell necrosis ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%